The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1200/jco.2006.08.4061
|View full text |Cite
|
Sign up to set email alerts
|

Activated Intrinsic Apoptosis Pathway Is a Key Related Prognostic Parameter in Acute Myeloid Leukemia

Abstract: High expression of both pro- and antiapoptotic genes predicted poor OS, which postulates a mechanism of activation of the apoptosis pathway as a whole. This mechanism, which culminates in a three-gene expression signature, allows accurate clinical outcome prediction in AML and puts efforts to target single antiapoptosis genes in a new perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 18 publications
1
33
0
1
Order By: Relevance
“…This has been previously observed in an independent cohort of AML and chronic myeloid leukemia patients. 42,48 It is assumed that the increased expression of antiapoptotic genes, leading to oncogene addiction, is counterbalanced by elevated expression of proapoptotic genes, thus creating a "primed to cell death" status. 49 In our present study, we observed increased expression of TAK1 in a large panel of AML CD34…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been previously observed in an independent cohort of AML and chronic myeloid leukemia patients. 42,48 It is assumed that the increased expression of antiapoptotic genes, leading to oncogene addiction, is counterbalanced by elevated expression of proapoptotic genes, thus creating a "primed to cell death" status. 49 In our present study, we observed increased expression of TAK1 in a large panel of AML CD34…”
Section: Discussionmentioning
confidence: 99%
“…39 Overexpression of multiple antiapoptotic genes of the mitochondrial related BCL-2 family has been related to the development and/or maintenance of AML and is prognostically significant for the treatment outcome of this group of patients. [40][41][42][43][44][45][46][47] By comparing the apoptotic gene profile of AML CD34…”
Section: Discussionmentioning
confidence: 99%
“…46 Gene expression profiling analyzing 31 apoptosis-related transcripts in newly diagnosed AML patients identified a threegene expression signature, including c-IAP2, to accurately predict poor overall survival. 49 Surprisingly, high expression of two pro-apoptotic genes, that is, BAX-(l) and BMF, also correlated with unfavorable survival besides c-IAP2. 49 This indicates that the prognostic impact of this gene signature may be due to an altered balance of pro-and anti-apoptotic genes.…”
mentioning
confidence: 99%
“…49 Surprisingly, high expression of two pro-apoptotic genes, that is, BAX-(l) and BMF, also correlated with unfavorable survival besides c-IAP2. 49 This indicates that the prognostic impact of this gene signature may be due to an altered balance of pro-and anti-apoptotic genes.…”
mentioning
confidence: 99%
“…2 On the contrary, studies assessing transcript levels of apoptosis signaling molecules showed inverse findings. 3 However, expression of single factors may not reflect the efficiency of the cell death machinery. For this reason we previously developed a different approach analyzing the functional integrity of apoptosis signaling in individual cells by simultaneously investigating 2 key apoptogenic events: mitochondrial release of cytochrome c and activation of caspase-3.…”
Section: Introductionmentioning
confidence: 99%